2008
DOI: 10.1049/iet-cdt:20070088
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous capture and shift power reduction test pattern generator for scan testing

Abstract: An automatic test pattern generation (ATPG) technique, which simultaneously reduces capture and shift power during scan testing, is presented. This ATPG performs power reduction during dynamic test compaction so the test length overhead is very small. This low-power test generator implements several novel techniques, such as parity backtrace, confined propagation, dynamic controllability and post-fill test regeneration. The experimental data on ISCAS benchmark circuits show that the peak capture power and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Because transient IR-drop analysis is very slow, past research often used alternative metrics, such as flip-flop toggle count (FFTC) [12]- [14] and weighted switching activity (WSA) [6], to estimate IR drop or test power. However, it has been shown that the above metrics do not correlate well with IR drop [15], [16]. To demonstrate this point, an experiment is conducted to show the correlations between average IR drop and these metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Because transient IR-drop analysis is very slow, past research often used alternative metrics, such as flip-flop toggle count (FFTC) [12]- [14] and weighted switching activity (WSA) [6], to estimate IR drop or test power. However, it has been shown that the above metrics do not correlate well with IR drop [15], [16]. To demonstrate this point, an experiment is conducted to show the correlations between average IR drop and these metrics.…”
Section: Introductionmentioning
confidence: 99%